Remission of Diabetes Mellitus during Pregnancy. Issue 5897 (12th January 1974) - Sheldon, Joanna; Coleman, Timothy
Abstract : Two cases are reported in which a remission of diabetes was sustained throughout pregnancy. This seemed to be due in part to improved β-cell function consequent on restoration of normoglycaemia before pregnancy, and in part to an increase in insulin sensitivity during pregnancy, which in the first case disappeared very rapidly after delivery.